All-share index in the Nigerian capital market responses to external financial flows shocks - Olawale Folorunsho Thomas; Adegbemi Babatunde Onakoya; Biola Phillip (International Journal of Management, Economics and Social Sciences (IJMESS), 2023)
Capital market remains an effective channel of financial intermediation. However, it has been underperforming in developing economies and thus resulting in the attendant illiquidity and other inefficiencies. This study examined the response of All-Share Index (ASI) to external financial flows shock since accessing capital from the capital market to augment the saving-investment gap has necessitated the high demand for external financial flows in Nigeria. The study employed data from 1981 to 2021 and the framework of impulse-response function and short-run pairwise Granger-causality approach were used. The finding showed that the impulse-responses of ASI for one-unit shocks to remittance from personal transfers, remittance from compensation of employees (RECE), trade openness and official development assistance (ODA) had noticeable positive impacts on ASI from the short to long-run. While shocks to FDI and FPI had negative impacts on ASI in the long-run. Also, the causal relationships were mixed-revealing across the time periods. The implication is that policymakers must develop policy directions to suit the time horizon of capital flows because the policy measures aimed at directing long-run capital inflows should not be the same as those aimed at changing the short-run patterns of flow in enhancing capital market performance.
Keywords: C59; E44; F30; 330; All-share index; capital market; external financial flows; impulse response function; Nigeria